2020
DOI: 10.1038/s41467-020-18879-7
|View full text |Cite
|
Sign up to set email alerts
|

Marine plankton show threshold extinction response to Neogene climate change

Abstract: Ongoing climate change is predicted to trigger major shifts in the geographic distribution of marine plankton species. However, it remains unclear whether species will successfully track optimal habitats to new regions, or face extinction. Here we show that one significant zooplankton group, the radiolaria, underwent a severe decline in high latitude species richness presaged by ecologic reorganization during the late Neogene, a time of amplified polar cooling. We find that the majority (71%) of affected speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Being species‐rich, intermediate‐to‐warm waters drive the overall extinction magnitude in our simulations, particularly depending on the ratio of tropical dispersal abilities to the temporal rate of warming. Dispersal abilities may have increased through time (Powell et al, 2015), but niche tracking failures during climate change may be more common than is generally assumed (Trubovitz et al, 2020). We did not include dispersal barriers (e.g., land, open ocean), thus our simulations may overestimate species geographical ranges, so that the results probably underestimate real world occupancy loss, particularly at lower latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Being species‐rich, intermediate‐to‐warm waters drive the overall extinction magnitude in our simulations, particularly depending on the ratio of tropical dispersal abilities to the temporal rate of warming. Dispersal abilities may have increased through time (Powell et al, 2015), but niche tracking failures during climate change may be more common than is generally assumed (Trubovitz et al, 2020). We did not include dispersal barriers (e.g., land, open ocean), thus our simulations may overestimate species geographical ranges, so that the results probably underestimate real world occupancy loss, particularly at lower latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal discharge, along elevated temperatures due to climate change, may negatively affect the marine organisms. There have been accounts showing that powerplant discharges have a negative effect on plankton communities (Chuang et al 2009;Choi et al 2012), and recent studies have observed that marine plankton may go extinct due to climate change (Trubovitz et al 2020), and elevated carbon dioxide has multiple impacts on the energy transfer and nutrient and carbon cycling of coastal marine ciliates (Biswas et al 2012). Additional study of the biological responses of marine organisms in the area of Masinloc-Oyon Bay affected by the powerplant discharge is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although longterm observations of microzooplankton are scarce, fossil records may offer some insights into the responses to climate trends. For instance, paleontological records of Polycystina (radiolaria) revealed that only one third of species were able to track optimal environmental conditions over the last 10 million years in the Southern Ocean [170].…”
Section: Latitudinal Range Shift and Temporal Redistributionmentioning
confidence: 99%